Farm diversification options for ensuring livelihood security of peri-urban farmers in eastern plateau and hill region: Learnings from Farmer FIRST Project - Kumar, Priya Ranjan; Maurya, Sudarshan; Chakrabarti, Asit; Yadav, V K; Naskar, Soumen; Gupta, Sanju; Kumari, Sonal; Singh, Arun Kumar; Bhatt, B P; Das, Bikash (The Indian Journal of Agricultural Sciences, 2020)
The research work was undertaken in four villages near Ranchi, Jharkhand under the Farmer FIRST Project to test the effectiveness of the technological options in improving the profitability of peri-urban agriculture system. Based on Principal Component Analysis of data on agri-economic conditions of farmers, the farm households could be classified into five broad typologies, viz. 1: Marginal farmers and landless labourers, 2: Cereal dominated small farmers, 3: IFS based small farmers, 4: Livestock based marginal farmers and 5: Cereal based medium farmers. Results of two years of experimentation indicated promising technological options like rainy season cultivation of solanaceous vegetables, cultivation of crops like wheat, chickpea and other rabi and summer season vegetables in rice fallow, management of ecto- and endo parasite in the animals and supplementation of area specific mineral mixture, cultivation of oyster mushroom for increasing income from agricultural production system. The project has resulted in increase in income of all typologies of farmers with a maximum increase in case of small farmers practising integrated farming and minimum increase in case of marginal farmers and landless labourers. Notably, income from non-farm sources saw a decrease in all five typologies.